Do grão ao pão: significações do alimento na pedagogia Waldorf - Machado, Juliana Gil da Silva (2016)
This research presents the differents meanings of food in Waldorf Education, according to its practices, based on the speech of mothers and teachers of a Waldorf School in the city of Fortaleza, as well as in the observations of this mother-reasercher. There was a previous search from the literature used by the own school in the studies of their teachers and the creation of their Curriculum, in the matters of School Food and possible Food and Nutritional Education. The method of reaserch chosen was the qualitative, according to MINAYO (1994). After the field research, the collected data was analysed under the modern theories of Curriculum, observing a possible hidden Curriculum, quoting Apple, and it was inferred that the practices follow the orientations of Steiner, founder of Waldorf Education, but are distant from the goals he meant to achieve, of looking at each child individually, because the school enphasys on the aspect of a group meal.